Learning Apache Flink : discover the definitive guide to crafting lightning-fast data processing for distributed systems with Apache Flink /: discover the definitive guide to crafting lightning-fast data processing for distributed systems with Apache Flink. ([2017]) - Deshpande, Tanmay
No abstract available